Perspektif Yuridis Standar Pengupahan Tenaga Kerja Era Pandemi Covid-19 - Gatot Satrio Utomo; Galih Raspati (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
This study is intended to determine the existence of legal protection and certainty for workers or employees related to the issue of wage standards for workers or employees during the Covid-19 pandemic. The Normative Method as a literature review used in this research outlines the contents of Article 88 paragraph (1) of Law no. 11 of 2020 concerning Work Copyright which states: explaining the right to employee benefits that arise automatically if there is a work correlation between workers and employers and at the time of termination of employment. The results of the study argue that insofar as there is security and guarantee of standard work wages for workers or employees in their work environment, employers or companies can delay payment of wages if the employer or company cannot pay compensation indicated by the lowest wage standards permitted by law, with the regulation. minimum wage standards to workers or trade unions identified by suspension. The postponement of the smallest wage installments by the company owner to workers or employees who can automatically decide the commitment or work contract from the entrepreneur/organization to pay the smallest difference in wages during the suspension period. With the Covid-19, the government issued Circular No. M/3/HK.04/III/2020 concerning Manpower Protection and Business Development in the context of preventing Covid-19. With the aim that the issuance of this regulation is necessary to legally protect and guarantee minimum wage standards and create work harmony between workers and employers. .